Women Dealing with The Law in Religious Courts - Muhammad Isna Wahyudi (Universitas Islam Negeri Jakarta, 2018)
Religious Courts in Indonesia which have special jurisdiction to hear disputes among Muslims are directly involved with the issue of women dealing with the law. Most of the Indonesian women seeking justice in religious court. Hence, it is important to discuss the application of justice and gender equality perspective in religious courts involving women dealing with the law. Employing justice and gender equality perspective, the author discusses some crucial issues including divorce, female witness, child marriage, joint property, polygamy, child custody, child denial, and paternity. It argues that such discussion is important as guidance to judges of religious courts in applying Supreme Court Regulation (PERMA) No. 3/2017 on Guidelines for Hearing the Case of Women Dealing with the Law.